Appointment reminder systems and patient preferences: Patient technology usage and familiarity with other service providers as predictive variables. (June 2013) - Finkelstein, Stacey R; Liu, Nan; Jani, Beena; Rosenthal, David; Poghosyan, Lusine
This study had two aims: to measure patient preferences for medical appointment reminder systems and to assess the predictive value of patient usage and familiarity with other service providers contacting them on responsiveness to appointment reminder systems. We used a cross-sectional design wherein patients' at an urban, primary-care clinic ranked various reminder systems and indicated their usage of technology and familiarity with other service providers contacting them over text messages and e-mails. We assessed the impact of patient usage of text messages and e-mails and patient familiarity with other service providers contacting them over text messages and e-mails on effectiveness of and responsiveness to appointment reminder systems. We found that patient usage of text messages or e-mails and familiarity with other service providers contacting them are the best predictors of perceived effectiveness and responsiveness to text message and e-mail reminders. When these variables are accounted for, age and other demographic variables do not predict responsiveness to reminder systems.